Integrate Analysis of Eyestalk Proteome and Metabolome in Precocious and Formal Juvenile Female Eriocheir sinensis - Tingshuang Pan; Min Yang; Tong Li; He Jiang; Jun Ling (Fishes)
The Chinese mitten crab (Eriocheir sinensis) is an economically important crustacean. With the development of the E. sisnensis industry, precocity has become a significant challenge in juvenile crab culturing. In this study, the eyestalks of female E. sinensis from precocious (PE) and normal juvenile (NE) groups were used for proteome and metabolome analyses. In total, 731 up-regulated and 657 down-regulated differentially expressed proteins (DEPs) were identified in the PE and NE groups. In addition, 110 differentially expressed metabolites (DMs) were up-regulated and 256 were down-regulated in the PE group. An integrated analysis showed 5667 significant correlations between the metabolites and proteins and 109 common pathways in the proteome and metabolome. The proteins were mostly associated with the mechanistic target of rapamycin (mTOR) pathway, longevity regulation, autophagy, and the pyrimidine and purine metabolism pathways. The metabolites were primarily enriched in amino acid and lipid metabolisms. These results demonstrated the differences in the PE and NE groups at two omics levels and will be useful for the E. sinensis industry.